PELATIHAN PEMANFAATAN SAMPAH KERTAS MENJADI KERTAS DAUR ULANG DAN SAMPAH PLASTIK MENJADI TAS RAJUT - Nyayu Neti Arianti; Ellys Yuliarti; M. Mustopa Romdhon (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The women members of the PKK in the Lokasi Baru Village, Air Periukan Subdistrict, Seluma Regency, Bengkulu Province have productive and useful activities, namely processing used newsprint into items such as baskets and flower vases and having knitting skills. Items resulting from knitting activities include bags, tablecloths, mask connectors, and others. However, these activities face several problems, namely the lack of variety of models of processed paper and knitted goods produced. This activity aims to provide additional knowledge to PKK members on how to make alternative products other than the products produced so far, namely making recycled paper and making knitted bags with a combination of yarn and plastic bag waste. The method used in this activity is counseling and direct practice (learning by doing). PKK members participated in the activity enthusiastically. It is hoped that after this training, PKK mothers will gain additional insight into the goods that can be produced from waste utilization activities. In addition to helping save the environment, this activity can generate additional income for households.